The Metamorphic Influence of Cause-Related Marketing : Empowering Consumers as Catalysts for Societal Transformation - Bhagat, Shikha; Sarvani, Shilpa; Rama Prasad, M. V. (Indian Journal of Marketing, 2024)
Purpose : In a market where prices and quality are fiercely competitive, companies have overflowed the market with a number of suitable brands. In the competitive business world of today, marketing tactics must always evolve to meet changing times and circumstances. Researchers have been motivated to discover the underlying aspects driving cause-related marketing strategy due to its global acceptability. This research elucidated the concept of cause-related marketing and emphasized the elements that motivate consumers to engage in such initiatives and influence their choice of products. Design/Methodology/Approach : The study was conducted with the help of a questionnaire sent to 480 respondents, out of which 432 questionnaires were found to be complete. Furthermore, the study examined the significance of each factor and its impact on decision-making using the confirmatory factor SEM model to analyze the data. Findings : The study revealed that â€œCommitmentâ€ was the utmost preferred attribute for the preference of cause-related marketing products. Practical Implications : A competitive edge may be obtained through cause-related marketing. Companies may provide financial support, increased awareness, and motivated actions for significant causes by making the most of their resources and efforts. This collaborative effort between companies and consumers has the potential to improve society significantly. Originality : The confirmatory factor SEM model has been used in this work to address urgent problems, new trends, or important information gaps.